Effect of the hour-1 bundle on clinical outcomes in patients with sepsis and septic shock: A protocol for systematic review and meta-analysis - Shukun Hong; Hongye Wang; Xiaoguang Fan; Jian Liu; Lujun Qiao (PLoS ONE, 2025)
Background According to the 2018 bundle guidelines of the Surviving Sepsis Campaign, many emergency departments and intensive care units currently adopt the hour-1 bundle as a standard practice for sepsis management. However, recent studies on the hour-1 bundle for sepsis treatment have yielded inconsistent results, raising questions and challenges about its clinical efficacy. Aim This study will conduct a systematic review and meta-analysis to compare the impact of the hour-1 bundle and non-hour-1 bundle on the clinical outcomes in patients with sepsis and septic shock. Methods The protocol was prepared according to the guidelines of the Preferred Reporting Items for Systematic Reviews and Meta-analyses protocol (PRISMA-P) statement. The systematic review will be carried out in line with the statement of PRISMA. The following electronic databases will be searched: PubMed, EMBASE, Cochrane Central Register of Controlled Trials, and Web of Science. All clinical studies comparing the impact of the hour-1 bundle and non-hour-1 bundle on clinical outcomes in patients with sepsis and septic shock will be included. All stages of the literature search, study selection, data extraction, and quality assessment will be conducted independently by two reviewers. Any disagreements between the two reviewers will be resolved by discussion or arbitration by a third reviewer. The primary outcome will be short-term mortality, which involves in-hospital, 28-day, 30-day, and 90-day mortality corresponding to the definition used in each study. For quality assessment, the risk of bias specified by the Cochrane Collaboration and the methodological index for non-randomized studies will be used for randomized control trials (RCTs) and non-RCTs, respectively. Data synthesis will be performed via Review Manager 5.1.0. Expected results This systematic review will integrate all relevant studies to quantitatively estimate the effect size and clarify the role of the hour-1 bundle in sepsis management, contributing new evidence-based guidance to the field. Systematic review registration Protocol registration and reporting: PROSPERO CRD42024579314.